Consumer protection institutions strengthening in the digitalization era - Kerti, N.G.N. Renti Maharaini (Indonesian Journal of Multidisciplinary Science, 2023)
Consumer protection laws have been in effect in Indonesia for 23 years, but consumer complaints seem to never end and even tend to increase. According to National Consumer Protection Agency (BPKN) complaint data, the three sectors with the most consumer complaints in the last five years have been financial services, e-commerce, and housing, as well as health services, transportation, telecommunications, food and beverage, cosmetics, and household gas electricity. Business transactions and dispute resolution are affected by information and technology improvements. Since the disruptive transaction system has transitioned from manual transaction patterns in traditional markets to digital transactions in online marketplaces, institutional strengthening of consumer protection is urgently needed. Strengthening consumer protection institutions is a genuine problem in the context of future consumer protection laws. Economic policy is measured not only by increasing output but also by increasing public consumption as a result of consumer confidence in the goods and/or services available on the market, which ultimately drives the rate of productivity growth to realize the welfare of Indonesian consumers. The importance of strengthening consumer protection institutions as a form of development and certainty of legal protection for consumers to realize consumer empowerment both individually and communally, as well as business actor compliance as an internal form of good corporate governance in consumer-centric change management governance.